2016
DOI: 10.1177/1753425916664125
|View full text |Cite
|
Sign up to set email alerts
|

IL-21 inhibits IL-17A-producing γδ T-cell response after infection with Bacillus Calmette-Guérin via induction of apoptosis

Abstract: Innate γδ T cells expressing Vγ6 produce IL-17A at an early stage following infection with Mycobacterium bovis Bacillus Calmette-Guérin (BCG). In this study, we used IL-21 receptor knockout (IL-21R KO) mice and IL-21-producing recombinant BCG mice (rBCG-Ag85B-IL-21) to examine the role of IL-21 in the regulation of IL-17A-producing innate γδ T-cell response following BCG infection. IL-17A-producing Vγ6 γδ T cells increased in the peritoneal cavity of IL-21R KO mice more than in wild type mice after BCG infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…20 TCR γδ T cells can be one of the main sources of IL-17 responding to IL-23 stimulation. 52 Our studies recently showed that IL-23 and other Th17-related cytokines can induce proliferation and expansion of Vγ2Vδ2 T cells in the presence of HMBPP. 23 Mycobacteria vaccination/infection of macaques enhances the ability of IL-23 to expand HMBPP-activated Vγ2Vδ2 T cells, and those expanded cells have multieffector functions for producing cytokines of IL-17, IL-22, IL-2 and IFN-γ.…”
Section: Interleukin-21mentioning
confidence: 87%
“…20 TCR γδ T cells can be one of the main sources of IL-17 responding to IL-23 stimulation. 52 Our studies recently showed that IL-23 and other Th17-related cytokines can induce proliferation and expansion of Vγ2Vδ2 T cells in the presence of HMBPP. 23 Mycobacteria vaccination/infection of macaques enhances the ability of IL-23 to expand HMBPP-activated Vγ2Vδ2 T cells, and those expanded cells have multieffector functions for producing cytokines of IL-17, IL-22, IL-2 and IFN-γ.…”
Section: Interleukin-21mentioning
confidence: 87%
“…There are also some cytokines in the TME that enhance the antitumor function of γδ T cells and inhibit the protumor γδ T cells responses. As IL-21 has been proven capable of inhibiting γδ T 17 cell protumor cell responses, further research on IL-21 should be conducted in human cancer [ 106 ]. It has been shown that IL-36γ acts synergistically with TCR signaling and/or that IL-12 can stimulate γδ T cells.…”
Section: Prospects For γδ T Cell-based Immunotherapiesmentioning
confidence: 99%
“…OVA-expressing recombinant BCG (rBCG-OVA) has been described previously (43). To construct rBCG-Ag85B-IL-21 or rBCG-Ag85B, pNN2-mIL-21-Ag85B or pNN2-Ag85B was introduced into BCG (strain Tokyo 172) by electroporation as reported previously (42,44,47).…”
Section: Methodsmentioning
confidence: 99%
“…Bacterial infection. The culture method for rBCG-OVA, rBCG-Ag85B-IL-21, or rBCG-Ag85B has been described previously (42,48). Mice were inoculated intratracheally (i.t.)…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation